Korelasi Antara Nilai CBR Dan Nilai Kuat Geser Sebagai Tanah Timbun - Albajili, Farian; Fatnanta, Ferry; Nugroho, Soewignyo Agus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
In constructing the roadway, subgrade is the important part to supporting the whole traffic load/construction load above. The bearing capacity of subgrade influences the flexible pavement, if bearing capacity is higher, then the application of flexible pavement is fewer to support the traffic load. Subgrade is affected by type of soil, density of soil, water content and others (Hendarsin, 2000). Generally, design of parking area uses the geometric design of road method. This case is inappropriate with actual condition, because the load support to parking area is static load. Nowdays, parking area planning uses CBR's data, while CBR is used to dynamic load estimation. Therefore, this research will be doing study about correlation between CBR value and UCS. Keyword : CBR, UCS, correlation